Reply to “racial and gender disparities among patients with Takotsubo syndrome” - Lemor, Alejandro (2019)
We read with great interest the Letter to the Editor titled “Racial and Gender Disparities among Patients with Takotsubo Syndrome” by Khalid et al regarding our recent publication. Their excellent comments and detailed assessment highlights the low prevalence of diabetes mellitus in patients with Takotsubo syndrome (TTS) compared to general population. This is in contrast with relatively high prevalence of many other cardiovascular risk factors in TTS patients. This so called “diabetes paradox” has been previously explained in TTS patients and is the target of many active investigations. As highlighted in the Letter to the Editor, the prevalence of diabetes mellitus in our patient population is very close to the results of prior meta‐analyses of multiple small studies of patients with TTS.